Some thoughts on approaches to export promotion in CARICOM - Bennett, Karl M. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2008)
Highlights the principal shortcomings in export promotion strategies pursued by countries in the region. Outlines a series of initiatives to address the identified shortcomings.